2022
DOI: 10.1172/jci.insight.152102
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-sensitive nephrotic syndrome candidate gene CLVS1 regulates podocyte oxidative stress and endocytosis

Abstract: We performed next generation sequencing in patients with familial steroid sensitive nephrotic syndrome (SSNS) and identified a homozygous segregating variant (p.H310Y) in the gene encoding clavesin-1 (CLVS1) in a consanguineous family with three affected individuals.Knockdown of the clavesin gene in zebrafish (clvs2) produced edema phenotypes due to disruption of podocyte structure and loss of glomerular filtration barrier integrity that can be rescued by WT CLVS1 but not the p.H310Y variant. Analysis of cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 81 publications
2
8
0
Order By: Relevance
“…In NS, podocyte injury and GBM thickening can lead to proteinuria. 37 In this study, results of the glomerular ultrastructure in the ADR group revealed severe fusion of the foot process and thickening of the GBM. HU significantly alleviated both these changes, and was more effective in doing so than U (Fig.…”
Section: Resultssupporting
confidence: 47%
“…In NS, podocyte injury and GBM thickening can lead to proteinuria. 37 In this study, results of the glomerular ultrastructure in the ADR group revealed severe fusion of the foot process and thickening of the GBM. HU significantly alleviated both these changes, and was more effective in doing so than U (Fig.…”
Section: Resultssupporting
confidence: 47%
“…In addition, CLDN7 was found upregulated in mouse pancreas exposed to caerylein for 12 h and its function concerned tight junction formation, while destruction of tight might be closely related with autophagy’s detrimental effects ( Nakada et al, 2010 ; Wang S. et al, 2020 ). So far CLVS1 wasn’t found significant in tumorigenesis and progression, but research found it is involved in lysosome maturation and associated with psychiatric and steroid-sensitive nephrotic syndrome ( Corponi et al, 2019 ; Lane et al, 2021 ). GMIP is a protein coding gene that encodes ARHGAP family of Rho/Rac/Cdc42-like GTPase activating proteins.…”
Section: Discussionmentioning
confidence: 99%
“…We applied our standard filtering algorithm ( Figure 2 ) ( 20 ) and identified segregating compound heterozygous variants (1) c.1772G > T p.G591V, (2) c.2084T > C p.L695S in NUP93 in the two brothers ( Figure 3A ). Both variants, which occur in evolutionarily conserved amino acid residues, are rare with a minor allele frequency of < 0.00015 in the gnomAD database.…”
Section: Methodsmentioning
confidence: 99%